Gender, Race, and Politics in the Midwest Black Club Women in Illinois - Hendricks, Wanda (Indiana University Press, 1998)
During the thirty year period from 1890 to 1920, the African American club women in Illinois helped establish the largest national network of black club women in the country, The National Association of Colored Women, created hundreds of female associations, organized the only federation of its kind in the state, The Illinois Federation of Colored Women, and cast ballots for the first black elected to the city council. Hendricks focuses on the Progressive Era, a period of numerous and unusual challenges not replicated in other regions of the country. Illinois and several of the other Midwestern states were affected by the burgeoning industrial economy and by the massive immigration of African American seeking economic opportunity. Chicago, by 1920, housed one of the largest and most urbanized black communities in the country. While few legal social and political restrictions were imposed on blacks, the state was the site of some of the worst race riots in the nation during the first two decades of the twentieth century. Club women successfully met these challenges by becoming social and political agents of reform and community uplift. Through their own volunteerism and fundraising they combated the problems of homelessness, unemployment, illiteracy, high mortality, and inadequate health care that plagued African Americans. They opened kindergartens, day nurseries, orphanages, settlement houses, elderly homes, recreation centers, and medical care facilities. They also demonstrated their political prowess by developing a gendered political culture. They formed suffrage clubs, entered public debates on major issues and voiced their opinions on the importance of holding politicians accountable for their actions. The Illinois club women also played a primary role in the election of Oscar Stanton DePriest as the first black alderman in Chicago. Blacks in the Diaspora Series